A haemostatic agent delivery system for endoscopic neurosurgical procedures. - Waran, V.; Sek, K.; Bahuri, N.F.; Narayanan, P.; Chandran, H. (2011)
In endoscopic neurosurgery problems with haemostasis due to poor access exist. We have developed a system which allows the delivery of a variety of haemostatic agents in a more efficacious manner. The system has been used successfully in endoscopic skull base surgery and endoscopic surgery within the parenchyma of the brain using tube systems.